Tobacco smoke and all-cause mortality and premature death in China: a cohort study - Liang Zhang; Yonghong Ma; Ke Men; Chao Li; Zhuo Zhang; Guoshuai Shi (BMC, 2023)
Abstract Background Tobacco smoke is associated with several diseases, and identified as the second leading risk factor for death from any cause worldwide. The relationship of tobacco smoke to mortality or premature death is not yet available from contemporary cohorts after 2010 in China. This study aimed to investigate the smoking behavior and the relationship of tobacco smoke to mortality and premature death among a nationally representative cohort starting from 2011 in China. Methods The nationally representative datasets (China Health and Retirement Longitudinal Study, CHARLS, 2011-2012) was employed and linked with follow-up data (2013). CHARLS was an ongoing nationally representative survey, which longitudinally followed up subjects aged over 45 years. Smoking status (non-smoker, ex-smoker, smoker, pack-years of smoking, age at starting and ceasing smoking) was used as independent variable, and all-cause mortality, premature death (defined as mortality before age 72.7 years in men and 76.9 years in women) were used as dependent variables. The Cox's proportional hazards regression mode was used to estimate the effect of tobacco smoke and pack-years of smoking on all-cause mortality and premature death. Results A total of 16,701 subjects were included. The association between tobacco smoker (hazard ratio [HR] = 1.37, 95%CI = 1.02, 1.83) / ex-smoker (HR = 1.75, 95%CI = 1.24, 2.46) and all-cause mortality was significant. Tobacco smoker (HR = 1.58, 95%CI = 1.04, 2.39) and ex-smoker (HR = 2.25, 95%CI = 1.38, 3.66) was associated with increase in the risk of premature death. Pack-years of smoking ≥ 30 was associated with increased risk of premature death compared with non-smokers in total (HR = 1.59, 95%CI = 1.03, 2.43) and women (HR = 3.38, 95%CI = 1.22, 9.38). Additionally, our results also revealed that there was a linear trend between pack-years of smoking and premature death in total (P = 0.002) and women (P = 0.010). Conclusion This study found a negative effect of smoking status on all-cause mortality and premature death among a contemporary and nationally representative data in China. The correlation between pack-years of smoking and premature death and the trend of pack-years of smoking with premature death was also identified.